For whom the school bell tolls: conflicting voices inside an alternative high school. - Kim, Jeong-Hee (My University, 2011)
This article is a study of conflicting voices inside an alternative high school in Arizona. Voices of alternative schools are, quite often, not included in the discourse of curriculum reform even though the number of alternative schools is growing every year. Bakhtinian novelness of polyphony, chronotope, and carnival are incorporated into an arts-based,storied form of representation to provoke empathic understanding among readers. Multiple voices (polyphony) of the school are juxtaposed within a certain time and space (chronotope) while all the different voices are valued equally (carnival) to represent conflicting views on public alternative school experiences. The purpose of the article is to provide readers with vicarious access to tensions that exist in an alternative school, so that they may engage in questioning the nature and purpose of these spaces. In so doing, the study aims to promote dialogic conversations about “best practice” for disenfranchised students who are subject to experiencing educational inequalities in the current era of accountability and standardization.
Keywords: Alternative schools; Disenfranchised students; Bakhtinian novelness